Design, development and evaluation of novel equipment for compost stability tests - Nguyen, Thanh Dam; Nguyen, Canh Viet; Phung, Thi Vi; Nguyen, Manh Huy; Ta, Thi Thao; Duong, Hong Anh; Vasel, Jean-Luc; Pham Hung Viet, (Vietnam Journal of Science and Technology, 2024)
Compost stability is a significant quality indicator that needs to be determined before using compost as an organic fertiliser. In this work, a novel device for assessing compost stability based on the oxygen consumption (OC) method was successfully developed. The design of this prototype was created to effectively solve inherent limitations observed in commercially available equipment functioning on the same concept (Oxitop devices). The performance of the device was evaluated in the laboratory to determine the OC of two different types of compost samples (food waste and green compost). The data indicated that the device worked stably and accurately during the test. Between the two types of samples, the compost based on food waste had higher AT4 and OCmax values but with lower K values. According to the EU regulations, both types of samples were considered stable.